Associative Meaning In Toba Batak Song - Septia Nauli Rianna Br. Manalu; Elia Masa Gintings; I Wayan Dirgeyasa Tangkas (TRANSFORM : Journal of English Language Teaching and Learning, 2020)
The study dealed with the types of associative meaning in Toba Batak Song. The objectives of this study were to find out the types of associative meaning in Batak Toba song and to find out the meaning of associative in traditional song Batak Toba. This study was conducted by using descriptive qualitative method. The data were collected from traditional songs of Batak Toba which were about messages or advices from parents for the children. There were 8 traditional songs of Batak Toba. The study revealed 82 lyrics related to associative meaning. Those 82 lyrics consisted of 28 lyrics in colloctive meaning, 21 lyrics in affective meaning, 12 lyrics in social meaning, 6 lyrics in reflective meaning and 15 lyrics in collocative meaning.The most dominant type of associative meaning used in Batak Toba song was connotative meaning. The associative meaning expressed in traditional Batak Toba songs connotative meaning expressed to receive compliment, old, helpless, children for being aware where they came from, and remember all of the advices. Affective meaning expressed about feeling between parents and children. Reflective meaning expressedto lyrics which have multiple meaning in environment for instance death. Social meaning expressed to class social that happen inside in the lyric. And the last was connotative meaning which expressedthe rightness, and behavior.